Learning environment management for total language immersion in the classroom: A case study of thai education development - Manissaward Jintapitak (2018)
© 2017 American Scientific Publishers All rights reserved. In 21st century, developing countries especially those with a non-English official language, English is always the main learning barrier for people. It enhances students’ learning and enables them to have life-long learning via the second language particularly English. Theoretically, ages between 6–8 years is the best period for children to learning a second language regarding their physical development. In fact, Thai students in a rural area of Thailand, except Bangkok, cannot use English to communicate effectively with people who speak English. It is a good opportunity to dissolve the English literacy difficulty of Thai students. The students can learn English or other new language through information technology include mobile technology and language multimedia learning resources available on the Internet. ulMtimedia directly fasters students in the development of cognitive skills especially language learning. English or language teachers can facilitate their students by problem-based learning with suitable constructionism methods. This research therefore focuses on immersion education by using constructionism and aims to study the management of learning environment for total language immersion in the classroom. It is essential for developing the country to reform the traditional education system by technology at an affordable investment, while students can communicate primarily with particular emphasis on listening and speaking skills applying a preliminary discussion.